Successful Dostarlimab Rechallenge Following Pembrolizumab‐Induced Autoimmune Hemolytic Anemia: A Case Report - Zaid Khamis; Kai Wang; Mohammad Aldalahmeh; Salim Barakat; Nawaraj Adhikari; Raghad Khassawneh; Bhavya Misri; Dhar Meekoo (Clinical Case Reports)
ABSTRACT Immune checkpoint inhibitors (ICIs) have revolutionized cancer treatment, offering durable responses across multiple malignancies. However, these agents can trigger severe immune‐related adverse events (irAEs), including drug‐induced autoimmune hemolytic anemia (AIHA), which often necessitates treatment discontinuation. While management guidelines for irAEs are well established, the safety and feasibility of ICI rechallenge after resolution of severe hematologic toxicities remain poorly understood. We herein present a case of pembrolizumab‐induced warm autoimmune hemolytic anemia that was successfully rechallenged with dostarlimab. In this case report, we describe a 66‐year‐old female with a history of stage III C2 endometrial cancer who is status post total abdominal hysterectomy, bilateral salpingo‐oophorectomy, and omentectomy. She had completed six cycles of adjuvant chemotherapy with paclitaxel and carboplatin. At her 12‐month follow‐up, elevated CA‐125 levels and imaging (CT Abdomen Pelvis with PET/CT) indicated possible disease recurrence at the vaginal cuff. A subsequent vaginal biopsy confirmed relapse and recurrence of endometrioid adenocarcinoma with squamous differentiation. Given that the tumor is MMR deficient, the patient was started on pembrolizumab along with carboplatin and paclitaxel. However, after the third cycle, she developed IgG‐positive warm autoimmune hemolytic anemia, attributed to pembrolizumab, leading to the discontinuation of the drug. She was treated with steroids, resulting in the resolution of her AIHA, and was then re‐challenged with dostarlimab and is showing promising results thus far. Our case demonstrates that rechallenge with alternative immune checkpoint inhibitors may be feasible in selected patients who have experienced immune‐related adverse events. However, this decision requires careful consideration of multiple factors, including the type and severity of the initial immune‐related adverse event, the potential consequences of recurrence, and the availability of alternative treatment options.